Pelatihan Pembukuan Sederhana Bagi UMKM Se-Provinsi Bengkulu - Danang Adi Putra; Pratana Puspa Midiastuty; Rini Indriani; Robinson Robinson; Sriwidharmanelly Sriwidharmanelly (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Micro and Small Businesses play an important role in the progress of a region because the existence of MSMEs can absorb labor, thereby contributing significantly to reducing unemployment. Bengkulu Province has many MSMEs operating in various fields, but there are still many deficiencies in MSMEs in Bengkulu Province. One of them is that small business owners still underestimate the importance of bookkeeping and do not separate personal assets from business assets. Most of them tend to make decisions based on intuition and experience. The aim of Community Service Implementation (PKM) activities through simple bookkeeping training for small business actors is so that they can make systematic and orderly bookkeeping, so that income, expenses and profits can be measured, and business development can be known. The service implementation method was carried out three times with each meeting with different MSMEs. Each meeting consists of 30-40 MSMEs so that in total 100 MSMEs receive training. The results of this activity show an increase in the knowledge and skills of business actors in running their businesses through simple bookkeeping that is easy to implement, thereby increasing their motivation to work.